2020
DOI: 10.1007/s40264-020-01035-x
|View full text |Cite
|
Sign up to set email alerts
|

Global Safety Database Summary of COVID-19-Related Drug Utilization-Safety Surveillance: A Sponsor’s Perspective

Abstract: Introduction Evidence-based clinical data on coronavirus disease 2019 (COVID-19) pharmacotherapies are scarce . Objective This study documented and characterized COVID-19 cases reported in individuals receiving treatment with Pfizer pharmaceutical products and cases that reported use of Pfizer pharmaceutical products for COVID-19 treatment. Methods This retrospective observational review leveraged the Pfizer safety database co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…During a global emergency, making clever use of existing resources is a fundamental human impulse. The cavalier repurposing of hydroxychloroquine, chloroquine, and azithromycin during the coronavirus disease 2019 (COVID- 19) pandemic may have consequences [1], and not only have clinical trials decisively shown that these particular drugs lack effectiveness in this disease [2,3] but Beyzarov et al [4] have also provided empirical evidence of safety-related harms. Therefore, we would be wise to read this study in the context of a well-intentioned but tragically flawed global scramble for cures for COVID-19.…”
Section: Addressing Two Safety Concernsmentioning
confidence: 99%
See 4 more Smart Citations
“…During a global emergency, making clever use of existing resources is a fundamental human impulse. The cavalier repurposing of hydroxychloroquine, chloroquine, and azithromycin during the coronavirus disease 2019 (COVID- 19) pandemic may have consequences [1], and not only have clinical trials decisively shown that these particular drugs lack effectiveness in this disease [2,3] but Beyzarov et al [4] have also provided empirical evidence of safety-related harms. Therefore, we would be wise to read this study in the context of a well-intentioned but tragically flawed global scramble for cures for COVID-19.…”
Section: Addressing Two Safety Concernsmentioning
confidence: 99%
“…The study by Beyzarov et al [4] evaluates two questions of considerable importance to public health. The first is, "What are the consequences of off-label use of drugs such as hydroxychloroquine and azithromycin when treating COVID-19?…”
Section: Addressing Two Safety Concernsmentioning
confidence: 99%
See 3 more Smart Citations